Research progress of oral health in the elderly (老年人群口腔健康研究进展) - DU Yonglin (杜永琳); YAO Lan (姚兰); HU Mengjiao (胡梦姣); WANG Ting (王婷) (中西医结合护理)
With populations aging rapidly due to declining fertility rates and increasing life expectancy, oral health has been a neglected aspect of global health, and older people are representative of vulnerable groups heavily affected by oral diseases. This study describes the aging situation faced by China, the oral health status of the elderly, the necessity of maintaining oral health of the elderly and the connection between oral health and general health of the elderly. It systematically summarizes the oral health countermeasures taken by domestic and foreign countries in the face of population aging, and provides theoretical references for effective nursing measures for the oral health of the elderly in the future. (全球人口老龄化趋势加重, 老年人群是受口腔疾病严重影响的弱势群体的代表。本研究阐述了我国目前老年人群的口腔健康状况, 维护老年人口腔健康的必要性以及老年人的口腔健康和一般健康的联系, 系统概括了国内外面对人口老龄化所采取的口腔健康措施, 以期为建立完善的老年人口腔健康护理措施提供理论参考。)